2012
DOI: 10.3109/1547691x.2012.686533
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Ochratoxin A-induced immunotoxic effects by silymarin and vitamin E in White Leghorn cockerels

Abstract: Silymarin (SL) is the bioactive extract of the plant Silybum marianum and Vitamin E (VE) is an important anti-oxidant. The present study was designed to evaluate potential ameliorative effects of SL and VE against Ochratoxin A (OTA)induced immunotoxic effects in White Leghorn cockerels. One day-old birds were divided into 12 groups (20 birds/ group) and fed basal diets amended with OTA (1.0 or 2.0 mg/kg) alone or in combination with SL (10 g/kg) and/or VE (200 mg/kg) for 42 days. Immunological in situ response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 37 publications
4
12
0
Order By: Relevance
“…The in vivo lympho-proliferative response of the broilers indicated that OTA led to poorer responses to PHA-P. Elaroussi et al (2006) reported the similar decreased response in broilers fed OTA for 35 Days. The observed decrease in in situ phagocytic activity was also consistent with previous reports of Khatoon et al (2013) andul-Hassan et al (2011a,b,c). Taking together the effects seen here on granulocyte phagocytic function and the known effects on B-and T-lymphocytes, it is likely that OTA led to reduce titers of antibodies against the SRBC as a culmination of multiple effects on the function of key cells involved in processing of this antigen and ultimate generation of antibody against it.…”
Section: Discussionsupporting
confidence: 93%
“…The in vivo lympho-proliferative response of the broilers indicated that OTA led to poorer responses to PHA-P. Elaroussi et al (2006) reported the similar decreased response in broilers fed OTA for 35 Days. The observed decrease in in situ phagocytic activity was also consistent with previous reports of Khatoon et al (2013) andul-Hassan et al (2011a,b,c). Taking together the effects seen here on granulocyte phagocytic function and the known effects on B-and T-lymphocytes, it is likely that OTA led to reduce titers of antibodies against the SRBC as a culmination of multiple effects on the function of key cells involved in processing of this antigen and ultimate generation of antibody against it.…”
Section: Discussionsupporting
confidence: 93%
“…However, in feed SLsupplementation @ 250 mg.kg −1 lowered the serum activity of ALT and AST when compared to control. Similar hepatoprotective effects of SL have been reported in poultry in ochratoxins toxicity (Khatoon et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…The mitogen, ochratoxin A (OTA) was used at the rates of 0.15, 0.3 and 1.0mg/kg in this study for a period of 42 days and the selection of these levels was made on the basis of different available studies in which OTA was used in the diet at the rates ranging from 0.13 to 8.0 mg/kg feed in birds (Santin et al, 2002;Elaroussi et al, 2006;Khatoon et al, 2013;Abidin et al, 2013;Marin and Taranu. 2015).…”
Section: Discussionmentioning
confidence: 99%